An Empirical Study of Comparison Between the Capital Asset Pricing Model and the Fama-French Three Factor Model: Evidence From Taiwan Stock Market - YEH, YU-JEN (2006)
The present study adds to the scarce published Taiwan literature on the size effect, the book-to-market effect and the comparison of explanatory power between the Capital Asset Pricing Model (CAPM) and the Fama and French three-factor model. The current study investigates Taiwan stock market during the time period of July 1999 to June 2005, and finds that the three-factor model provides significantly improved explanatory power over the CAPM, and evidences that the size factor plays an important role in asset pricing for the Taiwan stock market.